2022
DOI: 10.3390/biomedicines10020370
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole Offsets Mutant ATXN3-Induced Motor Dysfunction by Targeting Dopamine D2 and Serotonin 1A and 2A Receptors in C. elegans

Abstract: The atypical antipsychotic aripiprazole is a Food and Drug Administration-approved drug for the treatment of psychotic, mood, and other psychiatric disorders. Previous drug discovery efforts pinpointed aripiprazole as an effective suppressor of Machado–Joseph disease (MJD) pathogenesis, as its administration resulted in a reduced abundance and aggregation of mutant Ataxin-3 (ATXN3) proteins. Dopamine partial agonism and functional selectivity have been proposed as the main pharmacological mechanism of action o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…Interestingly, the antipsychotic aripirazole, shown to decrease the levels of polyQ-expanded Atx3 in the brain of MJD transgenic mice without directly interfering with Atx3 fibril assembly in vitro [53], is a partial agonist of dopamine D2 receptors in mammals [54]. Recently, it has been demonstrated that dopamine D2-like receptors are partly responsible for aripiprazole-mediated improvement motor dysfunction in a C. elegans MJD model [55]. A therapeutic strategy relying on low doses of dopaminergic drugs to prevent NNI accumulation would counteract a possible impairment of the nigrostriatal dopaminergic system associated with MJD [56], a feature that was previously identified in both symptomatic and asymptomatic MJD disease gene carriers using single-photon emission computed tomography [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the antipsychotic aripirazole, shown to decrease the levels of polyQ-expanded Atx3 in the brain of MJD transgenic mice without directly interfering with Atx3 fibril assembly in vitro [53], is a partial agonist of dopamine D2 receptors in mammals [54]. Recently, it has been demonstrated that dopamine D2-like receptors are partly responsible for aripiprazole-mediated improvement motor dysfunction in a C. elegans MJD model [55]. A therapeutic strategy relying on low doses of dopaminergic drugs to prevent NNI accumulation would counteract a possible impairment of the nigrostriatal dopaminergic system associated with MJD [56], a feature that was previously identified in both symptomatic and asymptomatic MJD disease gene carriers using single-photon emission computed tomography [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…However, its complications such as headache and nausea occur in about 50% patients ( Ghanekar et al, 2022 ). Aripiprazole improves dyskinesia but has significant side effects, such as anxiety, nausea, and dizziness ( Jalles et al, 2022 ). The complex pathogenic mechanism and differences between subtypes, patients show the inadequacy of symptomatic treatment ( Yap et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…Aripiprazole, a widely used atypical antipsychotic drug, was shown to extend the lifespan of C. elegans via signaling through DOP-2, a dopamine D2-like receptor (D2R) expressed in worms [ 1 ]. The mechanisms of action of aripiprazole are similar to those of quetiapine, except that quetiapine is a D2R antagonist, whereas aripiprazole possesses an agonistic effect on D2R [ 3 , 4 , 5 ]. Therefore, it is plausible that the lifespan-shortening effect of quetiapine is also mediated by DOP-2.…”
Section: Introductionmentioning
confidence: 99%